(untitled) (Euro-Latin American Journal of Administrative Law, 2022)
The climate crisis brings with it environmental, social, and economic impacts, in addition to environmental ones. Within these social and economic impacts, the shelter context is one of the most alarming. Additionally, this crisis was coupled with the advent of the pandemic, which, in addition to the health crisis, widened the inequality gaps, harming the most vulnerable people. Faced with this situation, this article aims to analyze whether the current international legal framework offers straightforward solutions to the distress of climate migrants. In the end, it concludes that it is necessary to establish legal status for the environmental refugee. Such a status can combine the international human rights regime and experiences adopted in regional environmental protection systems. Environmental refugees are a reality and require a concrete response.